IMPLEMENTATION OF INTEGRATIVE HOLISTIC ECCE IN THE EARLY CHILDHOOD EDUCATION UNIT OF TUNAS RIMBA I KINDERGARTEN, WEST BOGOR DISTRICT, BOGOR CITY - Maryati; Imamah; Siti Rohimah; Mila Daniati; Jaslina; Siti Hanan Jamilah (International Conferences on Early Childhood Education Proceedings, 2024)
PAUD HI (Holistic Integrative) services cannot be separated from Early Childhood Education because they are a single unit and integrated with each other. Therefore, the Education Unit must include this service in the school activity program. Based on this, this study was conducted to see the extent of the application of PAUD HI in kindergartens. The data needed in this study are data related to the implementation of PAUD HI services. And obtained using interview, observation, and documentation data collection techniques. Data analysis uses qualitative descriptive analysis techniques, namely data reduction, data display, and research results and data verification. Based on the results of this study, it was found that TK Tunas Rimba I has organized PAUD HI services such as education services, health services, nutrition and care, parenting services, protection services, and welfare services. TK Tunas Rimba I has also collaborated with various parties in implementing PAUD HI including health workers (Puskesmas), Gens Consulting, Disdukcapil and parents of students. Although in its implementation there are programmed or in other words contained in the curriculum of the institution, there are also activities that are incidental.